ANALISIS PENGARUH MOTIVASI KERJA, KEPEMIMPINAN DAN BUDAYA ORGANISASI MELALUI KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA CV. KHARISMA JAYA SURABAYA - NARYANTI, IKA (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2013)
The success of an enterprise affected by job performance or working results achieved by an employee. Performance assessment needs to be done as objective as possible as it will motivate employees in conducting its activities motivation is indispensable in advancing the performance of employees of a company. Leadership means using influence to motivate employees to achieve organizational goals. With the leadership in an organization then will develop an organizational culture within the company. Someone in work will feel comfortable and high on companies when in his works gain job satisfaction according to what you want. This research aimed at work, to see the influence of motivation leadership and cultural organization through satisfaction work against the performance of an employee at CV. Kharisma Jaya Surabaya. In this study used is the conclusive research on the study of causal research. Sampling-taking techniques used are non probability sampling. The type of method used is the purposive sampling. The sample used was 150 employees of CV. Kharisma Jaya in Surabaya. Data were collected using a questionnaire. The technique used is the analysis of Structural Equation Models with of AMOS programs. The results of this analysis indicate that the motivation, leadership and organizational culture affects job satisfaction of employees of CV. Kharisma Jaya in Surabaya. Besides found also that employee performance CV. Kharisma Jaya Surabaya affected by motivation, leadership and satisfaction work, while culture organization cannot influence it.